2015
DOI: 10.1016/s1872-2067(14)60268-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Fe species distribution and acidity of Fe-ZSM-5 on the hydrothermal stability and SO2 and hydrocarbons durability in NH3-SCR reaction

Abstract: Fe-exchanged ZSM-5 catalysts prepared from Na + and H + forms of ZSM-5 were evaluated for the selective catalytic reduction of NOx by NH3 (NH3-SCR). Fe-H-ZSM-5 showed higher SCR activity than Fe-Na-ZSM-5 both when fresh and after hydrothermal aging at 750 °C in 5% H2O/air. The Fe species distribution and acidity of Fe-H-ZSM-5 and Fe-Na-ZSM-5 were found to be different. The dealumination of the zeolite framework of Fe-H-ZSM-5 during hydrothermal aging was found to be more severe compared with that of Fe-Na-ZSM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 39 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…For three fresh samples, it was observed that all of the identified diffraction peaks could be ascribed to the mixed phase of HZSM-5 and the related doped oxides (Cr 2 O 3 , Fe 2 O 3 , and CuO). 7,24,25 For used Cr−O/HZSM-5 catalysts and Fe−O/ HZSM-5, no phase transformations were observed in XRD patterns compared to the fresh samples. It was worth noting that there were several new diffraction peaks (2θ = 16.0, 32.4, 39.9, 40.2, 57.2°) that emerged for Cu−O/HZSM-5(s) after 300 min reaction, as marked in Figure 7(c).…”
Section: Methodsmentioning
confidence: 99%
“…For three fresh samples, it was observed that all of the identified diffraction peaks could be ascribed to the mixed phase of HZSM-5 and the related doped oxides (Cr 2 O 3 , Fe 2 O 3 , and CuO). 7,24,25 For used Cr−O/HZSM-5 catalysts and Fe−O/ HZSM-5, no phase transformations were observed in XRD patterns compared to the fresh samples. It was worth noting that there were several new diffraction peaks (2θ = 16.0, 32.4, 39.9, 40.2, 57.2°) that emerged for Cu−O/HZSM-5(s) after 300 min reaction, as marked in Figure 7(c).…”
Section: Methodsmentioning
confidence: 99%
“…Wang [11] also stated that the Fe 2 O 3 particles had a good performance during NO x elimination, where the highest NO x conversion reached 95%. Yang et al [12] claimed that α-Fe 2 O 3 had a poor SCR activity, while γ-Fe 2 O 3 had an excellent SCR activity at 200-350 • C. Meanwhile, it was also found that the further increase reaction temperature from 350 to 500 • C would suppress NOx conversion over γ-Fe 2 O 3 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The spectral series can be divided in three regions: the NH 4 + -chemisorption and Lewis acid sites region (1400-2000 cm −1 ), the N-H stretching region (2000-3500 cm −1 ) and the -OH stretching region (3500-4000 cm −1 ). In the first region, the absorption peaks at 1488 [28], 1745 [29,30] and 1946 cm −1 [30] show similar intensities among all samples and they are assigned to NH 4 + adsorbed on BASs. The peak at 1592 cm −1 , assigned to NH 3 adsorbed on Lewis sites [29], is more pronounced in the spectrum of the Al-silicalite sample and almost disappears in the spectrum of the Fe-silicalite sample.…”
Section: Nh 3 Adsorptionmentioning
confidence: 87%